Facile synthesis and crystal structure of aGa22R8 cluster - Linti, Gerald W.; Rodig, Alexander (Chemical communications, 2000)
A new metalloid cluster Ga22R8 with a central gallium atom exhibiting an unusual coordination number of 13 and the gallatetrahedrane Ga4R4 are obtained by reaction of ‘GaI’ with the lithium tris(trimethylsilyl)germanide Li(thf)3R.